THE ROLES OF DIFFERENT MODES OF PLANNING ON STUDENTS’ WRITING PERFORMANCE ACROSS LEARNING STYLES - Baroroh Rochmah (Language-Edu, 2020)
This study investigates whether different modes of planning help the students improve their writing performance across learning styles. It also tries to reveal which format of planning results in better writing performance and which learning styles improves students’ writing performance best. The design used in the present study was experimental research since it examined the effects of modes of planning (pre-task/PTP and within task planning/WTP) towards students’ writing performance across learning styles. The researcher took two classes of ten classes as the subjects of the research using a lottery. After that they were treated using a pre-test to determine whether they were homogenous or not. The data were taken from the following instruments: Writing test and GEFT. The scores of the students were analyzed using independent sample t-test. The findings show that PTP outperforms WTP, and there is no significant difference between Field Independent (FI) Learners and Field Dependent (FD) Learners. Thus, no matter the students’ learning styles, students have to be suggested to make a plan before writing a text with the guidance of the teacher. Key Words: Pre-Task Planning, Within Task Planning, Learning Styles,                          Writing Performance